PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MULTIMEDIA INTERAKTIF TERHADAP KEMAMPUAN MENULIS TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VIII SMP NEGERI 1 SETIA JANJI TAHUN AJARAN 2025/2026 - Ade Putri Mayang Sari; Rina Hayati Maulidiah (Smart Education, 2026)
This research is motivated by the low ability to write observation report texts of class VIII students of SMP Negeri 1 Setia Janji. This problem is caused by the lack of variety of learning models used by teachers and the minimal use of digital-based learning media that can increase students' interest, motivation and creativity in writing LHO Texts. This study aims to determine the effect of the Discovery Learning model assisted by Multimedia Add Text on the ability to write observation report texts of class VIII students of SMP Negeri 1 Setia Janji. The theoretical basis of this research includes the concept of the Discovery Learning model that emphasizes the process of independent knowledge discovery by students and the use of Multimedia Add Text as a medium in writing observation report texts in the learning process and student worksheets. This study uses a quantitative experimental method with a Posttest Control Group Design. The research sample consisted of 62 students consisting of 31 students in the control class and 31 students in the experimental class who were selected using a simple random sampling technique. The data collection technique was carried out through a test of the skills to write observation report texts. The results showed that the average value of the ability to write observation report texts in the experimental class was 86.29, while in the control class it was 74.03. The results of hypothesis testing using the t-test obtained a value of tₕᵢₜᵤₙg = 12.26, while tₜₐbₑₗ = 1.67 at a significance level of 5% and 2.39 at a significance level of 1%. Because tₕᵢₜᵤₙg > tₜₐbₑₗ (12.26 > 1.67), the alternative hypothesis (Ha) is accepted and the hypothesis (Ho) is accepted. It can be concluded that the Discovery Learning model assisted by Multimedia Add Text has a significant effect on the ability to write observation report texts of class VIII students of SMP Negeri 1 Setia Janji in the 2025/2026 academic year.